2012
DOI: 10.1007/s10072-012-1072-3
|View full text |Cite
|
Sign up to set email alerts
|

Late-onset cluster headache: some considerations about 73 cases

Abstract: Data in the literature on cluster headache (CH) indicate a mean age at onset of about 29-30 years; recently, however, cases have been reported with onset in old age. A review of age at onset in all CH patients (n = 693) followed at the University of Parma Headache Centre between 1976 and 2011 shows that 73 (10.5 %) patients began to suffer from CH after age 50. In these 73 patient, the gender (M:F) ratio was 1.4:1, while in the 620 patients with CH onset before age 50, it was 2.5:1. In the patients with CH ons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
1
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 8 publications
(10 reference statements)
2
15
1
5
Order By: Relevance
“…22,23 However, more recent data have suggested that there has been a decrease of male predominance. 8,26,27 Although there were several Western reports that addressed CH in women, reports of CH in the Asian population that specifically addressed CH in women are still scarce. Cluster Headache Survey undertaken in 2008 showed a male to female ratio of 2.6:1.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 However, more recent data have suggested that there has been a decrease of male predominance. 8,26,27 Although there were several Western reports that addressed CH in women, reports of CH in the Asian population that specifically addressed CH in women are still scarce. Cluster Headache Survey undertaken in 2008 showed a male to female ratio of 2.6:1.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, when evaluated separately, medication responses did not differ significantly between those whose headache subtype had transformed (ie, episodic only vs formerly chronic now episodic; chronic only vs formerly episodic now chronic; data not shown). Interestingly, for those who first develop cluster headache after age 50, a greater proportion than average is female and of the chronic type, which could pose challenges for this group. The Clusterbusters ® Medication Use survey included 20 subjects whose cluster headache began after age 50; 8 were female (40%) and 8 also had chronic cluster headache (40%), both percentages greater than those of the overall survey population.…”
Section: Discussionmentioning
confidence: 99%
“…Une étude amé-ricaine sur 1134 sujets avec un diagnostic d'AVF confirmé par un neurologue a montré que l'AVF débute entre 20 et 40 ans dans 50 % des cas et avant l'âge de 20 ans dans 35 % (grade B) [8]. Le début de l'AVF chez la femme se fait avec deux pics de fréquence : un plus précoce que chez l'homme et un second après l'âge de 50 ans (grade B) [9,10].…”
Section: Distribution Selon Le Sexe Et L'âgeunclassified
“…Ainsi, bien que rare, l'AVF est possible chez l'enfant dès 5 ans [45], la présentation clinique étant identique à celle de l'adulte [46]. Au-delà des AVF survenant après 50 ans, notamment chez la femme [10], l'apparition d'une authentique AVF chez des sujets âgés de plus de 65 ans est possible, mais elle reste exceptionnelle [47]. Du fait de leur rareté, les AVF apparaissant aux âges extrêmes de la vie doit être considérées avec une grande vigilance diagnostique, afin d'écarter une céphalée secondaire.…”
Section: Connaître Les Formes Cliniques De L'algie Vasculaire De La Funclassified